2016
DOI: 10.1002/adfm.201601348
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Anisotropic Magnetoresistance of Antiferromagnetic Epitaxial Bimetallic Films: Mn2Au and Mn2Au/Fe Bilayers

Abstract: wileyonlinelibrary.comtraditional wholly ferromagnetic (FM) spintronic devices. [1][2][3] The reduced stray fi elds and faster spin dynamics of antiferomagnitic elements would allow further miniaturization with less cross-talk leading to faster higher density memory. The fast-evolving fi eld of antiferromagnetic spintronics is being pursued on many fronts, Núñez et al. studied spin torque and giant magnetoresistance (MR) in antiferromagnetic metals, [ 4 ] Hals et al. derived a phenomenological theory for curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…As shown in the inset in Fig. 3b, the dual in-plane magnetic easy axes results are well in line with the predicted magnetic structure of the (002)oriented single-crystal Mn 2 Au [20,21,35]. By carrying out the in-plane harmonic Hall voltage response measurement in a reference sample with the structure of STO substrate/Mn 2 Au (25 nm)/Cu (1 nm)/Py (10 nm)/SiO 2 (4 nm), as shown in the Fig.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…As shown in the inset in Fig. 3b, the dual in-plane magnetic easy axes results are well in line with the predicted magnetic structure of the (002)oriented single-crystal Mn 2 Au [20,21,35]. By carrying out the in-plane harmonic Hall voltage response measurement in a reference sample with the structure of STO substrate/Mn 2 Au (25 nm)/Cu (1 nm)/Py (10 nm)/SiO 2 (4 nm), as shown in the Fig.…”
Section: Resultssupporting
confidence: 85%
“…Among potential AFM materials, the collinear Mn 2 Au material has a great possibility of providing large ξ DL since the gold atoms result in a strong spin-orbit coupling (SOC) [19,20]. Regarding previous studies on the ξ DL of Mn 2 Au film, Singh et al [21] reported a large ξ DL = 0.22 in a Mn 2 Au/CoFeB bilayer system.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to polycrystalline Mn 2 Au films grown by molecular beam epitaxy [29,30] and partially (001)-oriented Mn 2 Au films deposited by sputtering [31], experiments below attain quasi-epitaxial (103), (101) and (204) Mn 2 Au films, and demonstrate the orientation dependent Néel-order spin-orbit torque switching in single layer Mn 2 Au films with different switching features for different orientations.…”
Section: Introductionmentioning
confidence: 88%
“…The main issue to generate functional spin transport based on antiferromagnets is to manipulate and detect an AFM state. The AFM memory state has been examined in several studies using anisotropic magnetoresistance (AMR); however, it mostly requires complicated stacking geometry for unified spintronic functionality. Since the AFM metallic alloys were mostly adopted for the desired functionality, AMR effects in ohmic magnetic devices are ordinarily restricted to variation of a few percent, which motivated recent studies focusing on tunneling AMR .…”
mentioning
confidence: 99%